PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PENCEMARAN LINGKUNGAN HIDUP (DI DESA PUSAR KECAMATAN BATURAJA BARAT KABUPATEN OGAN KOMERING ULU) - Olivia Sianura; M Tamudin (Tazir, 2023)
ABSTRACT The background of this research is that cement mining activities by PT Semen Baturaja aim to meet the national demand for cement, especially in the South Sumatra region. This activity is actually in the context of fulfilling the State's duties in the welfare of the people, however this mining activity has an impact on the environment and the community around PT Semen Baturaja. Among the negative impacts are the reduced water reserves, the amount of dust caused by mining activities around Navel Village. This background inspired the writer to conduct research with the title "Law Enforcement Against Criminal Acts of Environmental Pollution (In Pusar Village, West Baturaja District, Ogan Komering Ulu District). The formulation of the problem in this research is 1. How is Law Enforcement Against Environmental Pollution Crimes (in Pusar Village, Baturaja Barat District, Ogan Komering Ulu Regency) 2. What is the perspective of Islamic Criminal Law in Enforcement of Environmental Pollution (in Pusar Village, Baturaja Barat District, Ogan Regency Komering Ulu). The method used in this research is normative-empirical with a qualitative approach. Observation data collection techniques, interviews, and literature study. The data analysis technique in this study uses a qualitative descriptive method with an inductive mindset that is arranged systematically, so that it becomes concrete data regarding the criminal act of environmental pollution by PT Semen Baturaja. The data source for this research is primary data, namely information derived from interviews and direct observation of research locations, while secondary data is data obtained from documentation or literature to complement primary data. Based on the results of this study, the authors conclude that law enforcement against criminal acts of environmental pollution (in Pusar Village, Baturaja Barat District, Ogan Komering Ulu Regency, is not running as it should, only subject to administrative sanctions, due to difficulty linking the perpetrators with little evidence and lack of concern the community towards the surrounding environment, while responsibility in the form of (CSR) is not optimally given Islamic Criminal Law Perspectives on criminal acts of environmental pollution in Pusar Village, Baturaja Barat District, Ogan Komering Ulu Regency, are given sanctions in the form of ta'zir where the punishment and levels are returned to judges whose purpose is to educate and provide a deterrent effect on perpetrators who pollute the environment. Keywords: law enforcement, crime, environmental pollution